The research of the gas-filled dough rheological characteristics - Telychkun, Yuliia; Telychkun, Volodymyr; Taran, Vitaly; Gubenia, Oleksii; Desyk, Mykola (My University, 2010)
We explored reological descriptions of yeast dough , which filled with carbon dioxide. For researches the methods of capillary viscometery are used. Dependence of tension on speed of change is got at different content of gas phase, and dependence of effective viscidity on speed of change.
Keywords: тісто; реологічні характеристики; в’язкість; тесто; реологические характеристики; вязкость; dough; rheological characteristics; viscosity; кафедра машин і апаратів харчових та фармацевтичних виробництв